Upper and lower bounds of integral operator defined by the fractional hypergeometric function - Ibrahim, Rabha W.; Ahmad, Muhammad Zaini; Al-Janaby, Hiba F. (Open mathematics (Warsaw, Poland), 2015)
In this article, we impose some studies with applications for generalized integral operators for normalized holomorphic functions. By using the further extension of the extended Gauss hypergeometric functions, new subclasses of analytic functions containing extended Noor integral operator are introduced. Some characteristics of these functions are imposed, involving coefficient bounds and distortion theorems. Further, sufficient conditions for subordination and superordination are illustrated.